2016
DOI: 10.1016/j.ultsonch.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically enhanced fractionation of milk fat in a litre-scale prototype vessel

Abstract: The ultrasonic fractionation of milk fat in whole milk to fractions with distinct particle size distributions was demonstrated using a stage-based ultrasound-enhanced gravity separation protocol. Firstly, a single stage ultrasound gravity separation was characterised after various sonication durations (5-20 min) with a mass balance, where defined volume partitions were removed across the height of the separation vessel to determine the fat content and size distribution of fat droplets. Subsequent trials using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
7
30
0
Order By: Relevance
“…In the context of particle separation and manipulation, this is critically important. For example, the separation of fat in milk systems, whereby large milk fat globules (i.e., Ω ≥ 20) collect together and rise to form cream, whereas the smaller ones (Ω < 5) remain suspended in the milk, confirming some of the conclusions of experiments conducted by Leong et al [38] The relative motion of two particles owing to the mutual induction of microstreaming was also calculated in a parameter range for the first time by Jalal [27]. It was found that spheres of sufficiently large size or high frequency (i.e., Ω ≥ 10) touch each other in a lateral configuration, as shown in Figure 5.…”
Section: Particle Separation and Manipulationsupporting
confidence: 79%
“…In the context of particle separation and manipulation, this is critically important. For example, the separation of fat in milk systems, whereby large milk fat globules (i.e., Ω ≥ 20) collect together and rise to form cream, whereas the smaller ones (Ω < 5) remain suspended in the milk, confirming some of the conclusions of experiments conducted by Leong et al [38] The relative motion of two particles owing to the mutual induction of microstreaming was also calculated in a parameter range for the first time by Jalal [27]. It was found that spheres of sufficiently large size or high frequency (i.e., Ω ≥ 10) touch each other in a lateral configuration, as shown in Figure 5.…”
Section: Particle Separation and Manipulationsupporting
confidence: 79%
“…Oguz et al (2016) reported that the thermosonication treatment did not influence proximate composition of samples. The potential application of ultrasonication is to enhance creaming of milk fat globules in milk emulsion system, enhance the fractionation of milk fat in dairy system and achieve the separation of larger fat globules from a smaller one (Juliano et al, 2013;Leong et al, 2016;Leong et al, 2014) The data of raw sample shows an insignificant increase (P>0.05) in the protein content in control (4.14%) to (4.19%) in the US treatment and also from TS treatment (4.19% and 4.20%), respectively. No further significant changes could be rated in protein content of the remainder of the ultrasonic treatment of the ultrasonic treatment (US) and thermosonication treatment (TS) ( Table 1).…”
Section: Impact Of Ultrasound On Milk Componentsmentioning
confidence: 99%
“…Wu et al (2000) Showed that the practical use of high amplitude ultrasound typically produced a good homogenization effect compared with conventional homogenization. (Juliano et al, 2013;Leong et al, 2014 andLeong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic selection of cows, variation in feeding regimes and changes in milking frequency have all been shown to have some size-related effects on MFG in the milk, these approaches commonly lack reproducibility and control over a desired size range and from an industrial standpoint, would be complex and long-term to implement (Logan et al, 2014;Timmen & Patton, 1988). Shear processing, using processes such as homogenisation, micro-fluidisation or high-power ultrasound is more efficient, tuneable and readily scalable but inevitably results in some degree of damage to the MFG membrane (MFGM) and the formation of complex emulsions with milk proteins (Koxholt, Eisenmann, & Hinrichs, 2001;Leong et al, 2016;Olson, White, & Richter, 2004). Sedimentation of smaller droplets can also be a problem in nano-emulsions and other formulations, where the use of additional emulsifiers and stabilisers may be necessary to compensate for the damage to the MFGM and the increased surface area : volume ratio of the globules (McClements, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%